2011
DOI: 10.1128/aac.01211-10
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Properties of the Marine Natural Product Marinopyrrole A against Methicillin-Resistant Staphylococcus aureus

Abstract: The ongoing spread of methicillin-resistant Staphylococcus aureus (MRSA) strains in hospital and community settings presents a great challenge to public health and illustrates the urgency of discovering new antibiotics. Marinopyrrole A is a member of a structurally novel class of compounds identified from a species of marine-derived streptomycetes with evidence of antistaphylococcal activity. We show that marinopyrrole A has potent concentration-dependent bactericidal activity against clinically relevant hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(74 citation statements)
references
References 22 publications
3
71
0
Order By: Relevance
“…63 Further investigation showed (M)-28 had inhibitory activity against a wide range of MRSA strains and other gram-positive bacteria, as well as against the gram-negative Haemophilus influenza. 73 However, it was found that the therapeutic window for 28 is possibly too narrow for effective treatment, and that it is inactivated by human serum, thus potentially only be applicable in vivo as a topical agent. 73 That marinopyrrole A has shown a high affinity for binding to plastic indicates a potential use as a medical instrument coating agent to prevent infection, with the added bonus of lowered systemic toxicity from the aforementioned serum inactivation.…”
Section: Marinopyrroles: Determination Of Enzymatically-imposed Atropmentioning
confidence: 99%
See 1 more Smart Citation
“…63 Further investigation showed (M)-28 had inhibitory activity against a wide range of MRSA strains and other gram-positive bacteria, as well as against the gram-negative Haemophilus influenza. 73 However, it was found that the therapeutic window for 28 is possibly too narrow for effective treatment, and that it is inactivated by human serum, thus potentially only be applicable in vivo as a topical agent. 73 That marinopyrrole A has shown a high affinity for binding to plastic indicates a potential use as a medical instrument coating agent to prevent infection, with the added bonus of lowered systemic toxicity from the aforementioned serum inactivation.…”
Section: Marinopyrroles: Determination Of Enzymatically-imposed Atropmentioning
confidence: 99%
“…73 However, it was found that the therapeutic window for 28 is possibly too narrow for effective treatment, and that it is inactivated by human serum, thus potentially only be applicable in vivo as a topical agent. 73 That marinopyrrole A has shown a high affinity for binding to plastic indicates a potential use as a medical instrument coating agent to prevent infection, with the added bonus of lowered systemic toxicity from the aforementioned serum inactivation. 61 However, chlorinated and fluorinated derivatives have been generated exhibiting comparable MRSA inhibition and some resistance to serum inactivation, and thus may have future applications.…”
Section: Marinopyrroles: Determination Of Enzymatically-imposed Atropmentioning
confidence: 99%
“…(Haste, et al, 2011; Hughes, et al, 2009; Nicolaou, et al, 2011) Marinopyrrole A, which was named Maritoclax, was found to also selectively bind to Mcl-1 (IC 50 = 10.1 µM, Bim-BH3, ELISA), decrease Mcl-1 protein levels via proteasomal degradation and induce apoptosis in Mcl-1-dependent, but not Bcl-2- and Bcl-X L -dependent, leukemia(Doi, et al, 2012) and melanoma cells(Pandey, et al, 2013). However, Eichhorn and coworkers disclosed that marinopyrrole A was equally effective against Bcl-2-dependent leukemia cells compared to Mcl-1-dependent cells, and that treatment with marinopyrrole A had no effect upon Mcl-1 expression levels.…”
Section: Marinopyrrole a (Maritoclax)mentioning
confidence: 99%
“…(8). Bacterial viability was determined using an optical plate reader (at an optical density at 600 nm [OD 600 ]) and resazurin indicator dye as previously described (9).…”
Section: Methodsmentioning
confidence: 99%